Parasitic Eyeworm (Oxyspirura Petrowi) in Northern Bobwhites from the Rolling Plains of Texas, 2007–2011 - Stacie M. Villarreal; Alan M. Fedynich; Leonard A. Brennan; Dale Rollins (National Quail Symposium Proceedings, 2017)
The eyeworm Oxyspirura petrowi is an indirect life cycle nematode that occurs under the nictitating membrane on the eye surface of certain bird species. Previous studies from western or northwestern regions of Texas reported O. petrowi from northern bobwhites (Colinus virginianus), scaled quail (Callipepla squamata), and Montezuma quail (Cyrtonyx montezumae). We examined 173 bobwhites from the Rolling Plains of Texas collected during the 2007–2008 (n 1⁄4 33), 2009–2010 (n 1⁄4 86), and 2010–2011 (n 1⁄4 54) hunting seasons, respectively. Overall, 99 (57%) bobwhites were infected with 596 individual O. petrowi; the mean (6 SD) eyeworm intensity was 6.0 6 6.4 (range 1⁄4 1–40) and mean abundance was 3.4 6 5.7. Thus, this eyeworm is a commonly occurring parasite of bobwhites in the Rolling Plains of Texas. Additional surveys are needed to learn more about the geographic distribution of O. petrowi and to assess the possible negative effects on individual bobwhites and their populations.
Keywords: Colinus virginianus; eyeworm; helminth; northern bobwhite; Oxyspirura petrowi; Texas